2023
DOI: 10.3390/jfb14050274
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Alterations in Carbohydrate and Lipid Metabolism Due to Interactions with Nanomaterials

Abstract: Nanoparticles (NPs) have unique physicochemical properties that are useful for a broad range of biomedical and industrial applications; nevertheless, increasing concern exists about their biosafety. This review aims to focus on the implications of nanoparticles in cellular metabolism and their outcomes. In particular, some NPs have the ability to modify glucose and lipid metabolism, and this feature is especially interesting to treat diabetes and obesity and to target cancer cells. However, the lack of specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 108 publications
1
3
0
Order By: Relevance
“…The findings from this study on the hypolipidemic effect of R. officinalis have also been reported in previous studies [21,35,42]. An atherogenic diet and sedentary lifestyle are among the factors causing increased oxidative stress caused by the damage of cellular lipids, proteins, and carbohydrates [71,72]. Therefore, this study showed that the incorporation of ROP in the diet can have health benefits that can avert many non-communicable diseases (NCDs) such as diabetes, cancer, and cardiovascular diseases.…”
Section: Discussionsupporting
confidence: 83%
“…The findings from this study on the hypolipidemic effect of R. officinalis have also been reported in previous studies [21,35,42]. An atherogenic diet and sedentary lifestyle are among the factors causing increased oxidative stress caused by the damage of cellular lipids, proteins, and carbohydrates [71,72]. Therefore, this study showed that the incorporation of ROP in the diet can have health benefits that can avert many non-communicable diseases (NCDs) such as diabetes, cancer, and cardiovascular diseases.…”
Section: Discussionsupporting
confidence: 83%
“…The immune system of women with breast cancer and undergoing breast cancer surgery is usually compromised. In addition, tumor cells contain antigens that are related to the blood such as Lewis antigens like glycoproteins or glycolipids [35]. Disobedience of cancer cells might be caused by altered structural formation of carbohydrates with lipids or proteins [36].…”
Section: Tainted Immune Response In Breast Cancermentioning
confidence: 99%
“…The rapid development of these peculiar materials in a great variety of fields, however, has led to the need for exhaustive biodistribution and toxicity studies of each specific nanomaterial [6]. Currently, the precise interactions between these material and cells…”
Section: Introductionmentioning
confidence: 99%
“…The rapid development of these peculiar materials in a great variety of fields, however, has led to the need for exhaustive biodistribution and toxicity studies of each specific nanomaterial [6]. Currently, the precise interactions between these material and cells are not completely understood; key factors such as the size, surface charge or specific functionalization are involved in the cytotoxic effects [7].…”
Section: Introductionmentioning
confidence: 99%